2021
DOI: 10.1186/s13099-021-00458-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic characterization of multidrug-resistant Citrobacter spp. strains in Fennec fox imported to China

Abstract: Background To investigate the antimicrobial profiles and genomic characteristics of MDR-Citrobacter spp. strains isolated from Fennec fox imported from Sudan to China. Methods Four Citrobacter spp. strains were isolated from stool samples. Individual fresh stool samples were collected and subsequently diluted in phosphate buffered saline as described previously. The diluted fecal samples were plated on MacConkey agar supplemented with 1 mg/l cefota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Moreover, recent studies on the C. werkmanii strain BF-6 have demonstrated that OmpA plays an important role in the regulation of multiple virulence phenotypes, including biofilm formation on distinct surfaces, swimming motility, metal ion responses, and resistance to biocides [ 75 ]. Finally, the virulence typing analyses of C. werkmanii indicated the presence of the siderophore enterobactin genes for the acquisition of iron, an essential nutrient for bacteria growth and the increased virulence potential of Citrobacter [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies on the C. werkmanii strain BF-6 have demonstrated that OmpA plays an important role in the regulation of multiple virulence phenotypes, including biofilm formation on distinct surfaces, swimming motility, metal ion responses, and resistance to biocides [ 75 ]. Finally, the virulence typing analyses of C. werkmanii indicated the presence of the siderophore enterobactin genes for the acquisition of iron, an essential nutrient for bacteria growth and the increased virulence potential of Citrobacter [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…can act as a reservoir of AMR and CR genes with the ability to disseminate them to other species. Citrobacter species have been observed carrying MGEs containing genes imparting resistance to aminoglycosides, tetracyclines (TETs), and trimethoprim (Qin et al., 2021). Furthermore, prominent carbapenemase genes, including KPC, NDM, and OXA‐48, have been detected alongside other AMR genes within MGEs found in species of Citrobacter (Yao et al., 2021).…”
Section: Carbapenemase‐producing Enterobacteriaceaementioning
confidence: 99%
“… Citrobacter cronae was first described in 2020, following its isolation from rectal swabs of immunocompromised patients in Germany ( 1 ). Antimicrobial-resistant (AR) strains of C. cronae have been isolated from fennec fox ( Vulpes zerda ) imported into China from Sudan and from termites and fruits in Senegal ( 4 , 5 ).…”
Section: Announcementmentioning
confidence: 99%
“…Moreover, our strain contained several AR genes, including bla CMY-98 and qnrB12 . C. cronae ST141, isolated from fennec fox, contains bla CMY-98 ( 4 ). No mobile genetic elements were detected.…”
Section: Announcementmentioning
confidence: 99%